1994
DOI: 10.1136/bmj.308.6935.1015
|View full text |Cite
|
Sign up to set email alerts
|

Salivary diagnosis of measles: a study of notified cases in the United Kingdom, 1991-3

Abstract: Objectives-To validate a method for salivary diagnosis of measles and to assess the diagnostic accuracy ofnotified cases ofmeasles.Design-Blood and saliva samples were collected within 90 Conclusions-The existing national surveillance system for measles, which relies on clinically diagnosed cases, lacks the precision required for effective disease control. Saliva is a valid alternative to serum for IgM detection, and salivary diagnosis could play a major role in achieving measles elimination. Rubella and par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
73
1
3

Year Published

1995
1995
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 125 publications
(78 citation statements)
references
References 10 publications
1
73
1
3
Order By: Relevance
“…This is reminiscent of a previous study using saliva to diagnose measles where only a minority of the rash illness reported as measles could be confirmed by the average II days after onset. As expected, during an laboratory [3], illustrating the inaccuracy of clinical diagnosis of childhood exanthems. Assays for B19 infection should, therefore, be included in the surveillance of measles and rubella based on salivary testing.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…This is reminiscent of a previous study using saliva to diagnose measles where only a minority of the rash illness reported as measles could be confirmed by the average II days after onset. As expected, during an laboratory [3], illustrating the inaccuracy of clinical diagnosis of childhood exanthems. Assays for B19 infection should, therefore, be included in the surveillance of measles and rubella based on salivary testing.…”
Section: Discussionsupporting
confidence: 79%
“…Saliva was collected with a specially designed foam swab by wiping the swab along the gingival margin as described previously [3]. Fluid collected by this method, although referred to as saliva, is actually a transudate of plasma proteins and therefore reflects antibody responses in blood [4].…”
Section: Sample Collectionmentioning
confidence: 99%
“…The value of this vaccine efficacy, p, is set at 90 %. This is at the lower limit of most published estimates, which are based upon clinical diagnosis [25] [15,26,27]. The proportion of susceptibles who, following vaccination, remain able to transmit the infection, 1-p, enter the vaccine failure class, Xv (Fig.…”
Section: Epiderntiological Parameter Assignmentsmentioning
confidence: 94%
“…In 1991 the model significantly underestimates cases in children of less than 2 years of age. However, some of this discrepancy can be accounted for by age-related inaccuracy in clinical diagnosis recently identified by a PHLS study [15]. Whilst it is probable that there has always been a level of misdiagnosis in reported cases which is biased towards the youngest age classes, its importance will have increased with the decline in the circulation of measles accompanying high MMR vaccine coverage, and with the sporadic nature of measles infection.…”
Section: Predicted Impact Offuture Vaccination Policiesmentioning
confidence: 99%
See 1 more Smart Citation